Antarctica - The Superlative Continent - Ghosh, Amal Kumar (Modern Advances in Geography, Environment and Earth Sciences Vol. 3, 2021)
Antarctica, the south polar continent is unique in all esteem from physiographic, climatic, and biologic to noospheric wonders. It is the cosmopolitan region of broad-based research arena for the benefit of humankind. The earthly realm with scarce soil cover supports minimum moss, lichen and abundant algae from floral sphere and few species of insects, birds and amphibians from faunal domain within this harsh no own-man’s land, although Antarctic Ocean is full of lives for huge oxygen supplement. These provide ample food addendum to the aquatic as well as semi-terrestrial higher animal species. It is the only unique dome to be adorned with so many of utmost adjectives. The present study helps to undermine the inimitabilities and its importance in the field of science in addition with courageous expeditions to unveil it again to the present world.